The impact of rainfall and cypermethrin insecticides factors on the pollinating weevils (Elaeidobius Kamerunicus) population / Elmi Afidah Ibrahim - Ibrahim, Elmi Afidah (Faculty of Plantation and Agrotechnology, 2018)
Oil palm is one of the biggest markets that give the contributions of the country production and income. Malaysia becomes the largest producers and exporters of the palm oil in the world that have 4.49 million hectares of oil palm plantation. Indonesia become the biggest exporter of oil palm on 2008 and takes the title of our country as the biggest exporter at that time. To ensure the production of the oil palm can fulfill the demands, the country should know the way to increase the production. For example, like pollination by the weevils or other. The pollinator that have been focused in this study is the weevils that known as Elaeidobius kamerunicus. The weevil Elaeidobius kamerunicus is the African Pollinating weevils where actually is introduced from the Africa into the oil palm on Sabah around 1981. The relationship or the interaction of the pollinator and the host plant is very important to take precautions because it may increase the production or the yield of the oil palm. This is shown on the first establish where it can increase and improve the fruit set development and also increase the yield of the oil palm. Thus, the factors that may influence the population of these weevils should be identified. Rainfall factors make decreasing in the oil palm weevil’s population but it does not affect the efficiency and the ability to carry the pollen to the female inflorescence. While the cypermethrin insecticide give the positive relationship with the population of these weevils. That means the usage of the cypermethrin will decrease the population of these weevils. Thus, this paper reviews will review about factor that may reduce the population of the weevils thus reduces the yield of oil palm.